The impact of relational governance on performance improvement in export manufacturing firms - Usama Awan; Andrzej Kraslawski; Janne Huiskonen (Journal of Industrial Engineering and Management (JIEM), 2018)
Purpose: This paper seeks to identify the factors affecting social performance improvements in the Pakistan export manufacturing firms and investigate inter-relationships existing among them. Design/methodology/approach: This study used a cross-sectional survey; data were collected using self-administered survey questionnaire. Using data collected from 239 small- and medium-sized direct exporters manufacturing firms in Pakistan. We used structural equation modelling (SEM) approach to test structural model, and mediation analysis was conducted with regression analysis. Findings: The results support that meta-cognitive dimensions of cultural intelligence effect on social performance improvements, while the social performance improvement significant associated with innovation performance improvements. We suggest that cultural intelligence is a key to maintaining a relationship through development better cultural understanding and creating harmony among suppliers and buyers through minimizing the differences and disputes, requires developing social cohesion. Our results reveal that exporting firms need to adapt, reconfigure cultural knowledge and integrate resources into the operations to build learning capability, in turn, they can improve social performance and achieve superior innovation performance. Practical implications: Through the application of cultural intelligence capability, a firm could increase its ability to sense cultural differences, seize and adapt globally scattered cultural practices on social issues and allows for the development of unique knowledge resources and capabilities, impact on firm social performance and innovation performance improvements. Originality/value: The study conducted in Pakistan cultural context, which can be extended to other Asian countries. We argue that in a globalising world it is pertinent for exporting firms to have a better understanding of the various facets of cultural when dealing with inter-organisational relationships.
Keywords: 650; relational governance; cultural intelligence; social performance; innovation performance improvement; manufacturing firms